2010
DOI: 10.1002/pssc.200982631
|View full text |Cite
|
Sign up to set email alerts
|

Indium implantation and annealing of GaN: Lattice damage and recovery

Abstract: The effect of Indium (In) implantation in n‐type GaN is studied using Raman spectroscopy and Rutherford backscattering (RBS). The RBS analysis reveals that the 700 keV In implantation results in the formation of a subsurface defective region that extends to a depth of 400 nm. An abrupt increase (∼93%) of the maximum defect concentration is observed for fluences in the range 1.5 and 5×1014 cm‐2. A further increase of the fluence to 5×1015 cm‐2 renders the implanted layer amorphous. In the Raman spectra recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
(36 reference statements)
1
2
0
Order By: Relevance
“…Among some of the heavily implanted samples, the use of the third cumulant, c 3 , was found to be necessary in order to improve the fitting quality. The variation of the nn coordination numbers with Φ is consistent with the defect concentration determined with RBS [7]. More specifically, the defect concentration exhibits a twostep sigmoidal-like dependence on logΦ indicating the synergy of direct impact and defect accumulation mechanisms [11].…”
Section: Sample Preparation and Experimental Detailssupporting
confidence: 82%
See 1 more Smart Citation
“…Among some of the heavily implanted samples, the use of the third cumulant, c 3 , was found to be necessary in order to improve the fitting quality. The variation of the nn coordination numbers with Φ is consistent with the defect concentration determined with RBS [7]. More specifically, the defect concentration exhibits a twostep sigmoidal-like dependence on logΦ indicating the synergy of direct impact and defect accumulation mechanisms [11].…”
Section: Sample Preparation and Experimental Detailssupporting
confidence: 82%
“…Rutherford Backscattering (RBS) characterization has shown that ion implantation results in the formation of a highly defective layer extending throughout the GaN film. At fluences higher than 1×10 -15 cm -2 an amorphous layer that extends up to 200 nm from the surface is formed [7].…”
Section: Sample Preparation and Experimental Detailsmentioning
confidence: 99%
“…This can be demonstrated with n ‐type gallium nitride after its 700 keV indium implantation when a subsurface defective region was formed to a depth of 400 nm. The gradients depended on the indium fluencies and were analyzed by Rutherford backscattering and Raman spectra (Katsikini et al ., . The loading curves upon Berkovich ( R = 120 nm) indentation of Kavouras et al .…”
Section: Resultsmentioning
confidence: 97%